حل مشكلة المفاضلة بين الزمن والتكلفة والجودة في تخطيط المشاريع بتطبيق البرمجة بالأهداف الضبابية - مامو ،جبار; مكيديش ،محمد (جامعة الوادي University of Eloued, 2025)
Time-cost-quality trade-off in project planning is among the most important issues that interest the decision-maker, because the three elements of this trade-off are very important in the project and are located in an environment dominated by ambiguity and uncertainty in the future due to the circumstances surrounding the project. From it, the decision-maker can't set specific and accurate values for these three goals, so we used Fuzzy Goal Programming (FGP) using the (MinMax) method to solve a new proposed model of multi-objective linear programming (MOLP) of three goals different from the previously proposed models, which depends on activity instead of event and on paths instead of precedence relationships. this study contributes to formulating fuzzy goals of the decision-maker and giving an indication of the decision-maker's degree of satisfaction.
Solve Time-Cost-Quality trade-off problem by using MinMax Fuzzy goal programming Method
Keywords: برمجة بالأهداف الضبابية; برمجة خطية متعددة الأهداف; المفاضلة بين الزمن والتكلفة والجودة في المشروع; Fuzzy Goal programming; multi-objective linear programming; time-cost-quality trade-off